Institutions of Jewish Higher Religious Education in Abbasid Period: The Yeshivas - (:unkn) unknown (TURK TARIH KURUMU, 2015)
Due to painful experiences throughout history, Jews gave high importance to educational activity to keep their existance as a community. Yeshivas, where higher religious education was taught, were established in pre-Islamic period. During the Abbasid Period, Yeshivas of Sura and Pumbeditha in Iraq and Yeshiva of Palestine continued their activities without any obstacles. Yeshivas provided their economical expenses with the donations of the people affiliated. Help to yeshivas was considered among Jews a good deed, as same as help to the Temple of Solomon, when it still was. The donors to educational institutions were awarded with various pillars, such as honorary doctorate or something similar of today Besides of administrative task, yeshivas had others such as training for clergy, educating people, pursuing academic studies, replying (responsa) to questions of different Jewish communities and etc. The Gaons were the authority in the planning and implementation in yeshivas. Students who graduated from yeshivas were employed as a clergyman or director in community services. In Abbasid period there was a yeshiva in Jerusalem which belonged to Karaites too. Here students were educated as clergymen for Karaite communities who lived in different places of the world, mainly in Byzantium. This yeshiva was closed after Saljuks domination on Jerusalem (1071). Yeshivas have great influence for the Jews throughout history, surviving them from loosing their religious and ethnic identity. Students from the yeshivas had opportunity to spread their religious understandings in wide geography, besides the religious service to communities.
Keywords: Abbasids; Jews; Karaites; History of the Jews; Educational Institutions of the Jews; Jewish Academies; Karaite Academy; Yeshivas; History of Education; SOCIAL-SERVICES; COMMUNITY